2016
DOI: 10.1177/1756287216628784
|View full text |Cite
|
Sign up to set email alerts
|

Novel immunotherapeutic approaches to the treatment of urothelial carcinoma

Abstract: Abstract:Immunotherapy has long played a role in urothelial cancers with the use of bacille Calmette Guérin (BCG) being a mainstay in the treatment of nonmuscle invasive bladder cancer. Novel therapeutic approaches have not significantly impacted mortality in this population and so a renaissance in immunotherapy has resulted. This includes recombinant BCG, oncolytic viruses, monoclonal antibodies, vaccines, and adoptive T-cell therapy. Herein, we provide a review of the current state of the art and future ther… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
11
0
1

Year Published

2017
2017
2020
2020

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 72 publications
0
11
0
1
Order By: Relevance
“…Cell shrinkage, messenger RNA decay and DNA fragmentation are the most common changes within cell morphology due to apoptosis 11. It has been estimated that the number of cells, which undergo apoptosis in one day within a child (8-14 years old) is approximately 20-30 billion 12. Various techniques can be used to treat cancer which includes surgery,13,14 radiation,15 and chemotherapy 16.…”
mentioning
confidence: 99%
“…Cell shrinkage, messenger RNA decay and DNA fragmentation are the most common changes within cell morphology due to apoptosis 11. It has been estimated that the number of cells, which undergo apoptosis in one day within a child (8-14 years old) is approximately 20-30 billion 12. Various techniques can be used to treat cancer which includes surgery,13,14 radiation,15 and chemotherapy 16.…”
mentioning
confidence: 99%
“…Morphological observations of the tumor sections from the rBCG-immunized mice showed the infiltration of CD4 + T and CD8 + T lymphocytes into the tumor tissues. The average tumor volume in the rBCG group was less than the average tumor volume in the control group [29].…”
mentioning
confidence: 67%
“…These strategies have included IL-2, IL-12, IL-18, interferon (IFN-α), and IFN-γ secreting rBCG. [ 17 ] Studies have shown these strains can be effective in increasing IFN-γ production, improving antigen-specific proliferation, eliciting higher levels of Th1 cytokines, and enhancing antitumor activity. [ 18 19 20 21 22 ] Th1 cytokine-based rBCG strains may have the potential of enhancing BCG for treatment of NMIBC; further clinical trials in humans are necessary.…”
Section: Recombinant Bacillus Calmette–guerinmentioning
confidence: 99%